2016
DOI: 10.2147/vmrr.s68905
|View full text |Cite
|
Sign up to set email alerts
|

Infectious bursal disease virus in poultry: current status and future prospects

Abstract: Infectious bursal disease virus (IBDV) affects immature B lymphocytes of the bursa of Fabricius and may cause significant immunosuppression. It continues to be a leading cause of economic losses in the poultry industry. IBDV, having a segmented double-stranded RNA genome, is prone to genetic variation. Therefore, IBDV isolates with different genotypic and phenotypic diversity exist. Understanding these features of the virus and the mechanisms of protective immunity elicited thereof is necessary for developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 136 publications
(144 reference statements)
0
15
0
Order By: Relevance
“…It has been shown that vaccines prepared from cvIBDV strains provide partial protection against vvIBDV strains, ultimately allowing infection of vaccinated chickens, which then excrete the virulent viruses. This is considered one of the reasons for the appearance of mutant vaccine strains causing outbreaks in vaccinated flocks [2]. The adaptation of escape mutant vaccine strains in regions using vaccines prepared from cvIBDV strains alongside indigenous field strains has been reported [1,11].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that vaccines prepared from cvIBDV strains provide partial protection against vvIBDV strains, ultimately allowing infection of vaccinated chickens, which then excrete the virulent viruses. This is considered one of the reasons for the appearance of mutant vaccine strains causing outbreaks in vaccinated flocks [2]. The adaptation of escape mutant vaccine strains in regions using vaccines prepared from cvIBDV strains alongside indigenous field strains has been reported [1,11].…”
Section: Discussionmentioning
confidence: 99%
“…Infectious bursal disease (IBD), an immunosuppressive disease, caused by infectious bursal disease virus (IBDV) has always been a major concern for poultry farmers. IBDV can infect immature B-lymphocytes in the bursa of Fabricius (1) and result in vaccination failure and susceptibility of chickens to pathogens (2). Both maternal immunity and active immunity can protect chicks against IBDV infection.…”
Section: Introductionmentioning
confidence: 99%
“…These strains are grouped into four characteristic pathotypes including classical, attenuated, antigenic variant, and very virulent strains [ 12 14 ]. Nearly 60–76% of IBDV isolates across four continents can be grouped as very virulent based on the global molecular epidemiological investigations [ 15 ]. Since the first report of the very virulent IBDV (vvIBDV) in the USA in 1957 [ 12 , 16 ], the disease has been spreading worldwide [ 15 ] including Egypt [ 17 – 19 ] and has undergone a complex evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 60–76% of IBDV isolates across four continents can be grouped as very virulent based on the global molecular epidemiological investigations [ 15 ]. Since the first report of the very virulent IBDV (vvIBDV) in the USA in 1957 [ 12 , 16 ], the disease has been spreading worldwide [ 15 ] including Egypt [ 17 – 19 ] and has undergone a complex evolution. In Egypt, the vvIBDVs were first reported in 1989 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%